Proposed Project to strengthen the internal managerial capacity of the Interamerican Institute of Agricultural Sciences - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2021)
82 páginas.